Readiness for Implementation of the Halal Product Assurance System (SJPH) at Jambi City Slaughterhouses - Heni Pratiwi (Socrates: Journal of Education, Philosophy and Psychology, 2026)
This study aims to evaluate the readiness of Slaughterhouses (RPH) in Jambi City in obtaining halal certification based on the standards set by the Halal Product Guarantee Organizing Agency, as well as to identify aspects that need to be improved to increase consumer compliance and trust. This study employed a qualitative descriptive approach, collecting data through field observations, interviews, and documentation at a slaughterhouse (RPH) in Jambi City. The analysis was conducted by comparing the operational practices, facilities, and halal management implemented with the halal certification standards established by the Halal Product Assurance Agency (BPJH) to assess readiness and identify gaps.